Ensino-aprendizagem dos jogos esportivos coletivos: estabelecendo relações entre lógica interna e métodos de ensino - Silva, Carlos Santiago Cruz Menezes da (2023)
Collective Sports Games are characterized as driving practices of cooperation and opposition. These modalities have great popularity, being regularly practiced in the different contexts in which they are inserted. In the field of Physical Education, there is a predominance of this group of sports in relation to the others, which reflects the need for them to be developed in a way that is adequate to their internal logic. However, it is still possible to frequently find these driving practices being developed by traditional models that no longer offer the necessary support to conduct the teaching of these sports in accordance with their operating dynamics. In this way, the literature has been increasing its production regarding this theme, and thus, discussing the teaching-learning process of JECs and how improvements can be achieved considering their specific characteristics in comparison to other sports. From this, the study approaches a bibliographical research of exploratory character, proposals that aim to contribute with the teaching of sports in the role of surpassing forms of teaching based predominantly on the repetition of technical gestures without considering the logic of operation of these practices. Therefore, it is emphasized that the teaching of JECs must be guided by the internal logic that the group presents, as well as taking into account the specific logic of each modality. The study also exposes the methodological issue, emphasizing the importance of using methods, which are suitable for working with these sports, since they need to understand in their structure the norms and properties of the JECs, which makes this recurrent discussion about the importance of choice of methodological proposals compatible with certain characteristics. Thus, this dissertation seeks to highlight common points between the internal logic of the JECs and teaching methods that contemplate the dynamics of the game in its entirety. In this sense, this research presents the following problem: How to establish the relationship between internal logic and teaching methods of collective sports games? To obtain such an answer, the study dissects scientific knowledge in order to establish these relationships, and for the internal logic, emphasis is placed on Motor Praxiology, theory of games and sports that deals with analyzing their internal logic, having tools that provide theoretical support for understanding practices such as JECs. With regard to teaching methods, Situational and Conditional Games stand out, models that are part of the new trends that seek to overcome proposals that disregard tactical elements, for example. Through these theoretical foundations and the proximity in the conception of the JECs, relationships with a propositional character were established in terms of contributing to the literature in the area and providing theoretical support to organize the work in practice. Finally, it is shown that the articulation between the internal logic, guided by a theory of sports analysis, with teaching methods that consider it, promotes the teaching of JECs according to their specificities, demonstrating that complementary proposals with a good foundation are possibilities to help the work of teachers and coaches in learning spaces.